The Self-Care Needs and Behaviors of Dementia Informal Caregivers: A Systematic Review. (21st June 2018) - Waligora, Kyra J; Bahouth, Mona N; Han, Hae-Ra
Abstract: Background: More than 5.4 million informal caregivers (ICGs) in the United States care for persons with dementia (PWD). Failure of ICGs to incorporate self-care into their routine may lead to adverse health consequences. Caregivers and researchers need to understand the evidence around dementia ICGs' self-care practices. Purpose: To synthesize evidence on the self-care needs and behaviors of Alzheimer's and dementia ICGs and its research implications. Methods: PubMed, CINAHL, Scopus, and Web of Science were searched to conduct a systematic review of research. Orem's self-care theory and a concept analysis of self-management behaviors provided a framework for the review. Results: Three themes emerged from 29 included studies: self-care needs and behaviors of ICGs, barriers to performing self-care, and enablers of self-care. The self-care needs of dementia ICGs included sleep, social engagement and support, and leisure activities. Self-care behaviors identified by this review were engaging in activities with the PWD, spiritual and religious activities, and taking a break from caregiving. Barriers to self-care were gender roles, self-sacrificing, minority ethnicity, and burden of caregiving. Enabling self-care involved acknowledging personal consequences of caregiving, balancing self-care needs with the PWD's needs, and positioning oneself as an objective/subjective duality. Implications: Self-care is a dynamic, challenging aspect to caregiving, but supporting evidence is often limited or cannot be generalized. More studies are needed that include random sampling, heterogeneous samples, and quantitative methods. Additional research is needed to understand how self-care needs, behaviors, and barriers differ by caregiver race/ethnicity, gender, or relationship to the PWD.